Happy birthday? The euro at 20 - Kerstin Bernoth; Franziska Bremus; Geraldine Dany-Knedlik; Henrik Enderlein; Marcel Fratzscher; Lucas Guttenberg; Alexander Kriwoluzky; Rosa M. Lastra (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We analyse the first twenty years of the euro both from an economic and an institutional perspective. We find that in particular during the period since the financial crisis, convergence as measured by a variety of indicators has not improved. Design flaws in the Eurozone institutional architecture have contributed importantly to this lack of convergence. This is why further reforms are urgently needed.
Additional information: This policy contribution was prepared for the European Parliament Committee on Economic and Monetary Affairs ahead of the European Parliament's Monetary Dialogue in January 2019.
Keywords: 330